The long-term trend in contingent faculty employment: data report - Curtis, John W., author (Colorado State University. Libraries, 2021)
The national trend in academic employment status from 1975 to 2019. Includes separate tabulations for instructional staff, including graduate student employees, and faculty, broken out by institution type.
ZIP file includes XLSX spreadsheets.
Keywords: academic employment; faculty; diversity; race; gender; equity